Elevating the photodecolorization efficiency for synthetic and actual colored wastewater through the integration of chitosan and zinc oxide layers on a fiberglass flat sheets - Riki Subagyo; Saepurahman Saepurahman; Elfirza Zain; Sri Hartati; Lei Zhang; Kiki Adi Kurnia; Arramel Arramel; Ratna Ediati; Syafsir Akhlus; Yuly Kusumawati (Case Studies in Chemical and Environmental Engineering)
This study reported a novel technique for spray coating zinc oxide (ZnO) on one side of fiberglass (FG) substrate and chitosan (CS) on the opposite side, resulting in the production of ZnO/FG/CS composite. This strategy alters the morphology of the pure FG, creating smooth and rough surfaces on the CS and ZnO sides, respectively. ZnO/FG/CS demonstrated remarkable photoremoval activity in a combined solution of methylene blue-methyl orange and real wastewater with the addition of hydrogen peroxide and facilitated moderate reusability over five cycles. This strategy revealed an insight for developing an integrated adsorption and photocatalytic process with high-performance capabilities.